Paix, développement et droits de l'homme - Pettiti, Louis (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1987)
The author begins by presenting the institutional effort for development accomplished by the United Nations, the European Council, the European Community as well as that resulting from the A.C.P. Lomé Accords and the Helsinki Accord. The author then situates the right to development in the third generation of Human Rights, which are those of collective rights and examines the very concept of the right to development including all of its social implications.